2010
DOI: 10.1111/j.1365-2036.2009.04226.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood coeliac disease: towards an improved serological mass screening strategy

Abstract: SUMMARY BackgroundIn 1997-1998, 6127 asymptomatic children aged 2-4 years were screened for coeliac disease (CD) by anti-endomysium (EmA) testing in the Netherlands. After 6 (AE2) months, biopsies were performed in 57 seropositive children; 31(54%) had villous atrophy, but 26 (46%), all HLA-DQ2 ⁄ DQ8 positive, had normal histology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 24 publications
1
6
2
Order By: Relevance
“…These patients should not be classified as seronegative patients with CD, as some usually do in clinical practice because of low antibody titers (24). Our results are somewhat different from a Dutch study (16), where CD was diagnosed only in 54% of patients presenting fluctuating Receiver-operating characteristic (ROC) curve used to define the optimal cut-off of ULN for discriminating the presence of mucosal atrophy. The grey dot (sum of sensitivity and specificity) identifies 1 ULN as the mean value having a sensitivity of 99% (95% CI: 0.958-0.997) and a specificity of 64.9% (95% CI: 0.532-0.755) in predicting complete intestinal atrophy.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…These patients should not be classified as seronegative patients with CD, as some usually do in clinical practice because of low antibody titers (24). Our results are somewhat different from a Dutch study (16), where CD was diagnosed only in 54% of patients presenting fluctuating Receiver-operating characteristic (ROC) curve used to define the optimal cut-off of ULN for discriminating the presence of mucosal atrophy. The grey dot (sum of sensitivity and specificity) identifies 1 ULN as the mean value having a sensitivity of 99% (95% CI: 0.958-0.997) and a specificity of 64.9% (95% CI: 0.532-0.755) in predicting complete intestinal atrophy.…”
Section: Discussioncontrasting
confidence: 83%
“…In suspected CD with persistently low positive anti-TGA IgA titers, the role and timing of esophagogastroduodenoscopy (EGD) with duodenal biopsies represent a clinical challenge, considering a high risk of unspecific mucosal findings or unnecessary invasive procedures (15). Only few studies addressed this issue and tried to avoid unnecessary exams (16,17).…”
Section: What Is Newmentioning
confidence: 99%
“…Other studies, however, confirmed the manufacturer's cutoff of 20 as the optimal one in children both for screening and for follow-up after GFD (20), even in those with total IgA deficiency (24). On the contrary, some authors suggested raising the cutoff to 30 for a-DGP IgA, IgG, and IgAþG (25) or even to 45 for a-DGP IgAþG when used for CD mass screening (26). According to our cutoff, both a-DGP IgA and a-DGP IgAþG showed good sensitivity as screening tests for CD, but sensitivity was still lower than that of anti-tTG IgA.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of highly sensitive and specific serologic assays for CD has led to increased recognition that the disease is more common than assumed. Sugai et al 14 , 15 and Hogen Esch et al 16 reported that the IgA/IgG human-tTG/DGP enzyme-linked immunosorbent assay (ELISA) is one of the most sensitive screening tests for CD. Using an h-tTG/DGP combined ELISA, we carried out a study of serological screening for CD in adult Han Chinese patients with chronic diarrhea predominant IBS (IBS-D) that is the most frequent form of IBS and represents a high risk group to suffer from CD and healthy individuals.…”
Section: Introductionmentioning
confidence: 99%